TRANSPARENCY OF VITAE OF LEGISLATIVE CANDIDATES IN THE 2024 ELECTIONS: TRANSPARANSI DAFTAR RIWAYAT HIDUP CALON ANGGOTA LEGISLATIF DALAM PEMILU 2024 - Adisty, Septiani Jessica; Antikowati, Antikowati; Chandra, Ratih Listyana (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2025)
One of the information provided by the The General Election Commission a curriculum vitae of legislative candidates in the legislative elections. Historical life list information is useful for voters as material for consideration in determining their choice according to their preferences. In this article, we will examine how public information disclosure is implemented, especially the curriculum vitae of legislative candidates in the 2024 Legislative Election and how it will affect the The General Election Commission if it does not implement election information disclosure. The method used in this writing is normative juridical with a statutory and contextual approach. The research results show that in the 2024 Legislative Election the percentage of legislative candidates who open their curriculum vitae is greater than the legislative candidates who do not open their curriculum vitae. This phenomenon is caused by the absence of binding regulations that require legislative candidates to open a curriculum vitae. The General Election Commission gives each legislative candidate the freedom to open or not make a curriculum vitae. This step is a form of The General Election Commission effort to carry out public information disclosure. The General Election Commission will be subject to criminal sanctions if it does not carry out information disclosure in accordance with Public Information Openness Law.